Resistance to Bacterial Infection Induced by Statolon and Pyran - Pindak, Frank F. (1970)
The antibacterial properties of statolon and pyran were compared with those of bacterial endotoxin and found to be similar. Although high resistance was transient, it was followed by immunity of the same order as in mice infected without pre-treatment with the interferon inducers.